1046 The canadian injury prevention trainee network: building capacity for the future of injury prevention research. (1st September 2016) - Richmond, Sarah A; Black, Amanda M; Fridman, Liraz; Ezzat, Allison; Clemens, Tessa; Pike, Ian; Macpherson, Alison
Abstract : Background: Injuries are a serious but preventable health concern in Canada and a growing field of research, attracting a large number of graduate students and other trainees across Canada to identify injury prevention as their field of study. In 2009, the Canadian Institute for Health Research funded a team in Child and Youth (C&Y) Injury Prevention. With this support, the team was able to develop a model of practice involving researchers, stakeholders, knowledge users, and trainees as part of a multidisciplinary approach to reducing the burden of injury in youth. The C&Y team was successful at supporting and highlighting the work of over 40 team trainees. The efforts of this trainee team have resulted in the formation of the Canadian Injury Prevention Trainee Network (CIPTN). Objective: The CIPTN aims to build a network of trainees interested in the science and practice of injury prevention (IP) from a multi-disciplinary perspective. Specifically, the goals include increasing opportunities for collaboration, professional development, mentorship and networking. Results: The CIPTN has worked to develop a list of learning and research oriented catalyst activities for trainee members. The CIPTN has successfully collaborated with IP experts and organisations from across Canada in the development of a comprehensive IP resource, as well as updating the Canadian Injury Prevention Curriculum, a course for IP practitioners across Canada. Further, an executive board and governance structure has facilitated the identification of future collaborative activities (e.g., bi-monthly seminars, grant writing, and evaluating an injury methods workshop). Conclusions: The CIPTN increases opportunities for junior researchers and trainees to work within a network of colleagues to share research, build collaborative projects, expand capacity, and provide training opportunities. This in turn, will develop the quantity and quality of IP science and practice across Canada for future generations.